Cambios en los pliegues conjuntivales paralelos al párpado (LIPCOF) asociados al uso de lentes de contacto Hi-Si - Álvarez Portilla, Pablo Hernando (Universidad Antonio Nariño, 2022)
Management of soft contact lens discomfort (CLD, Contact lens discomfort) continues to be a challenge in clinical practice. There is more of 125 million contact lens wearers worldwide and around than 50% of them report having adverse ocular sensations, generally described as dry eyes.